2018
DOI: 10.56093/ijans.v88i3.78297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of Kankrej cattle through associated herd progeny testing under field and farm conditions

Abstract: The genetic improvement programme of Kankrej cattle under AICRP on Cattle is implemented in their home tract for their conservation and propagation. The involvement of farmer’s animal under the programme has helped to create awareness among the cattle breeders on the importance of this valuable breed. The production of frozen semen doses of genetically superior young bulls and providing the AI facility at the doorstep of the farmer has motivated and increased the conception rate to a large extent. The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Buffaloes are capable of breeding throughout the year, Nonetheless, the seasonal ovarian activity in several countries including Egypt makes the opportunity of buffaloes to get pregnant is time limited (Kandiel et al, 2013). Buffalo's estrus symptoms are less noticeable than those of cattle whereas the peak concentrations of progesterone and estradiol are less (Singh and Sahni, 1995). Field surveillance on reproductive disorders revealed that anestrus (in forms of prolonged calving interval and silent heat) was the primary factor in buffaloes' infertility particularly in Egypt (Fooda et al, 2011 andAhmed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Buffaloes are capable of breeding throughout the year, Nonetheless, the seasonal ovarian activity in several countries including Egypt makes the opportunity of buffaloes to get pregnant is time limited (Kandiel et al, 2013). Buffalo's estrus symptoms are less noticeable than those of cattle whereas the peak concentrations of progesterone and estradiol are less (Singh and Sahni, 1995). Field surveillance on reproductive disorders revealed that anestrus (in forms of prolonged calving interval and silent heat) was the primary factor in buffaloes' infertility particularly in Egypt (Fooda et al, 2011 andAhmed et al, 2011).…”
Section: Introductionmentioning
confidence: 99%